Perspective of a Pediatrician: Shared Pathogenesis of the Three Most Successful Pathogens of Children - Tuomanen, Elaine I. (Frontiers in Cellular and Infection Microbiology, 2020)
Highly successful invasive pathogens exploit host vulnerabilities by adapting tools to co-opt highly conserved host features. This is especially true when pathogens develop ligands to hijack trafficking routes or signaling patterns of host receptors. In this context, highly successful pathogens can be grouped together by the patterns of organs infected and diseases they cause. In the case of this perspective, the focus is on the historically most successful invasive bacterial pathogens of children that cause pneumonia, sepsis and meningitis: Streptococcus pneumoniae, Haemophilus influenzae, and Neisseria meningitidis. This triad shares a ligand to bind to PAF receptor to enter host cells despite early defenses by innate immunity. All three also target laminin receptor to cross endothelial barriers using a common set of molecular tools that may prove to be a design for a cross-protective vaccine.